The legal response to computer misuse in Malaysia - The Computer Crimes Act 1997 / Dr. Zaiton Hamin - Hamin, Zaiton (Faculty of Administratron and Law, 2004)
Malaysia is embarking onto a massive and ambitious plan to become a fully developed nation with a value-based society by the year 2020. The Prime Minster, Dr Mahathir, had laid down the groundwork for this government policy in 1991 with his announcement of Vision 2020. The government perceives the application of information and communication technologies across both Malaysian society and economy as a means of achieving these goals and symbols of success.1 Thus, the present thrust in Malaysia's development plans is to build a "knowledge-based economy" which leads to the establishment of a National IT Agenda (NITA) to formulate a combination of goals and means as the roles of information, knowledge and "echnopreneurship" working together to transform the economy into a "knowledge economy" (k-economy) and the society into a "knowledge society" (k-society).2 To achieve these broad aims a legislative platform or what is termed by NITA, as "infostructure" is needed. Six cyber laws involving digital signature, computer crimes, telemedicine, and electronic government, copyright and multimedia convergence have been identified as necessary and were created since 1997 3 jijg Computer Crimes Act 1997 was amongst the first to be enacted. It was published in the Gazette on 30 June 1997 and received Royal Assent on 18 June 1997. However, it only became enforceable three years later on 30 June 2000.